Substrate integrated waveguide microwave antenna and filter design using H-fractal unit cell - Hamzah, Ayad Muslim (2021)
Currently, the fifth generation (5G) technology has been assigned for microwave. There are several challenges in developing antennas and filters for 5G devices that need to be addressed such as low efficiency and large size at the lower proposed 5G frequency band (1 GHz -6 GHz). Hence, a compact size device and wideband are the main requirements for the lower 5G bands applications. To allow small package devices for lower 5G band technology, the antennas and filters should be small enough to maintain the integration of massive network and keep a good performance of the state of art devices. Generally, microstrip planar technology is used to implement the antennas and filters. However, due to the size and losses which come from using common microstrip technology that results in a poor performance of the proposed devices. Substrate integrated waveguide with H-shaped fractal unit cell is proposed in this work to overcome these challenges. The proposed antenna operates at 4 GHz and 5.7 GHz frequencies bands which suite the lower 5G applications. The proposed antenna was designed and simulated by using CST MWS formulations. The antenna is fabricated on Roger RO4003C substrate with thickness of 1.52 mm. The measured S11 of 10 dB, gain of 5.4 dB, and efficiency of 82 % are achieved at these two bands. The proposed antenna was miniaturized by using H-fractal unit cell. Meanwhile, filter performs centre frequency at 5 GHz with bandwidth of 1.2 GHz and the proposed filter was designed and simulated by using ADS software. The filter is realized on FR-4 substrate with thickness of 1.2 mm with very compact size of 0.12λ × 0.15λ is achieved with a reduction rate of 23%. The designed filter has an insertion loss of 0.75 mm with similar size of the antenna. However, there are some discrepancies appeared between the measured and simulated radiation pattern due to the losses from the measurement cables and the unwanted signal interferences since the measurement room is partially covered with absorbers. Nevertheless, the designed antenna and filter have a great potential for lower mm-wave and 5G band applications.